Interdomain linkers tailor the stability of immunoglobulin repeats in polyproteins - Joshi, Tanuja; Garg, Surbhi; Das, Sayan; Kammath, Anjana R.; Sagar, Amin; Rakshit, Sabyasachi (Elsevier, 2021)
Linkers in polyproteins are considered as mere spacers between two adjacent domains. However, a series of studies using single-molecule force spectroscopy have recently reported distinct thermodynamic stability of I27 in polyproteins with varying linkers and indicated the vital role of linkers in domain stability. A flexible glycine rich linker (-(GGG)n, n ≥ 3) featured unfolding at lower forces than the regularly used arg-ser (RS) based linker. Interdomain interactions among I27 domains in Gly-rich linkers were suggested to lead to reduced domain stability. However, the negative impact of inter domain interactions on domain stability is thermodynamically counter-intuitive and demanded thorough investigations. Here, using an array of ensemble equilibrium experiments and in-silico measurements with I27 singlet and doublets with two aforementioned linkers, we delineate that the inter-domain interactions in fact raise the stability of the polyprotein with RS linker. More surprisingly, a highly flexible Gly-rich linker has no interference on the stability of polyprotein. Overall, we conclude that flexible linkers are preferred in a polyprotein for maintaining domain’s independence.
Only IISERM authors are available in the record.
Keywords: Inter domain linkers (IDLs); Polyproteins; Domain stability; Protein thermodynamics; Structural propensity; Single molecule force spectroscopy(SMFS)